Clinical and genetic spectrum in 33 Egyptian families with suspected primary ciliary dyskinesia. Issue 3 (5th December 2019) - Fassad, Mahmoud R.; Shoman, Walaa I.; Morsy, Heba; Patel, Mitali P.; Radwan, Nesrine; Jenkins, Lucy; Cullup, Thomas; Fouda, Eman; Mitchison, Hannah M.; Fasseeh, Nader
Abstract: Primary ciliary dyskinesia (PCD) is a rare genetic disorder of motile cilia dysfunction generally inherited as an autosomal recessive disease. Genetic testing is increasingly considered an early step in the PCD diagnostic workflow. We used targeted panel next‐generation sequencing (NGS) for genetic screening of 33 Egyptian families with clinically highly suspected PCD. All variants prioritized were Sanger confirmed in the affected individuals and correctly segregated within the family. Targeted NGS yielded a high diagnostic output (70%) with biallelic mutations identified in known PCD genes. Mutations were identified in 13 genes overall, with CCDC40 and CCDC39 the most frequently mutated genes among Egyptian patients. Most identified mutations were predicted null effect variants (79%) and not reported before (85%). This study reveals that the genetic landscape of PCD among Egyptians is highly heterogeneous, indicating that a targeted NGS approach covering multiple genes will provide a superior diagnostic yield compared to Sanger sequencing for genetic diagnosis. The high diagnostic output achieved here highlights the potential of placing genetic testing early within the diagnostic workflow for PCD, in particular in developing countries where other diagnostic tests can be less available. Abstract :